Cytokine-induced killer cells/dendritic cells and cytokine-induced killer cells immunotherapy for the treatment of esophageal cancer: A meta-analysis. Issue 13 (2nd April 2021) - Yuan, Xin; Zhang, An Zhi; Ren, Yi Lin; Wang, Xue Li; Jiang, Chen Hao; Yang, Lan; Liu, Chun Xia; Liang, Wei Hua; Pang, Li Juan; Gu, Wen Yi; Li, Feng; Hu, Jian Ming
Abstract: Objectives: This meta-analysis was designed to systematically evaluate whether autologous cytokine-induced killer cells (CIK) or dendritic cells and cytokine-induced killer cells (DC-CIK) immunotherapy combined with chemotherapy can improve the therapeutic effect and safety of chemotherapy in esophageal cancer (EC). Materials and methods: Randomized controlled trials (RCTs) were electronically searched databases including CNKI, WanFang, WeiPu, CBMDisc, PubMed, Web of Science, EMbase, the Cochrane Library, and Clinical Trials. The databases were searched for articles published until June 2019. Two researchers independently screened the literature, extracted data, and evaluated the quality of the included literature. Meta-analysis was performed using RevMan5.3. Results: Seventeen studies (1416 participants) were included. The differences between CIK/DC-CIK combination chemotherapy and chemotherapy alone were significant. The results displayed that the number of CD3 +, CD4 +, CD4 + /CD8 +, and NK cells was significantly increased after 1 to 2 weeks of treatment with CIK/DC-CIK cells in the treatment group (all P < .05). In addition, the results shown that 1-year overall survival was significantly prolonged ( P < .0001) and quality of life was improved ( P = .001) in EC chemotherapy combined with immunotherapy groups compared with conventional treatment. Furthermore, cytokine expression levels of interleukin 2 (IL-2), tumor necrosis factor α (TNF-α), and interleukin 12 (IL-12) were significantly increased ( P = .0003) as well as the levels of immunoglobulins were elevated ( P < .00001). Serum levels of tumor marker molecules, carcinoembryonic antigen (CEA), carbohydrate antigen (CA)-199, and CA-125 were lower in treatment groups than that of control groups ( P < .00001). No fatal adverse reactions were noted ( P = .04). Conclusions: It is safe and effective for patients to use chemotherapy combined with CIK/DC-CIK immunotherapy. Immunotherapy can simultaneously improve the antitumor immune response. Specifically, DC-CIK cells can increase T lymphocyte subsets, CIK cells, NK cells, and immunoglobulins in peripheral blood to enhance antitumor immunity. Therefore, combination therapy enhances the immune function and improves the therapeutic efficacy of patients with EC.